WEB Based Geographic Information System For School Maping In Bungo District - Melky Ardiyansa; Fatima Felawati; Sepriano Sepriano (Sustainability (STPP) Theory, Practice and Policy, 2022)
The Bungo Regency Government has done several things in realizing the Sustainable Development Goals (SDGs) which are the current global focus that are mutually agreed upon, including Indonesia. This is intended to make the data easier to display. Displaying information in web form will make it easier for people to see it. The method in this research is the Waterfall method. In designing maps using Google Maps, the software used in building this application is PHP, HTML, CSS, as a programming language, MySQL as a database server, and Codeigniter. GIS mapping of education in Bungo Regency is a system that provides information to the public about the location of schools in Bungo Regency and their supporting facilities